(untitled) - Abun-Nasr, Jamil M. (Cambridge, 1987)
The author emphasises the factors which led to the adoption of Islam by practically the entire population, the geographical position of the area, which made it the main trade link between the Mediterranean world and the Sudan and led to its involvement in the confrontation between the Christian and Islamic worlds. In Morocco, this confrontation led to the emergence of a distinct religio-political community ruled by sharifian dynasties and, in the rest of the Maghrib, to integration in the Ottoman empire. The political and economic developments of the 'piratical' regencies of Algeria, Tunisia and Libya, the establishment of European colonial rule, the nationalist movements and Islamic religious reform are all treated in detail. The balance between factual account and interpretation makes the book especially useful to students of African and Islamic history.
Keywords: Bắc Phi; Lịch sứ